Students’ local musical studies: project method and its implementation - Dolgushina, Marina (Pedagogy and Psychology, 2021)
This article is dedicated to the use of the project method in musical and regional studies of the university students. The research was based on years of experience of teachers and students of the Federal State Budgetary Educational Institution of Higher Education "Vologda State University". Specifically, two types of student projects carried out in the course of studying the discipline "Musical culture of the Vologda region" were analysed: firstly, group projects related to the search for materials about musical life in periodicals of previous years, and secondly, individual projects based on verbal history methods. On the one hand, students’ projects are aimed at the development of the necessary professional competencies, and on the other hand, they contribute to the gradual filling of substantial gaps in the musical history of Vologda. Similarities are identified between the project method and the concept of learning by doing where each student is positioned as an active and creative subject of study. In addition, this research highlights a significant educational potential of music and local history work.